Peran Guru Dalam Mengembangkan Nilai Etika Dan Moral Peserta Didik Sekolah Dasar - Aini, Fauziah; Ramadhan, Zaka Hadikusuma (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Education is the main foundation in forming an individual's character, skills and knowledge, enabling them to overcome various challenges in life. In this context, teachers play an important role in developing students' ethical and moral values. Teachers not only function as transmitters of lesson material, but also as role models who inspire and guide students through examples of good behavior. The aim of this research is to examine and clarify the role of teachers in facilitating the ethical and moral development of students. In this research, researchers used narrative qualitative methods. This research uses a data analysis methodology which consists of several steps, namely data collection, data reduction and drawing conclusions or verification. Three techniques were used in data collection: observation, interviews and documentation. Based on research findings, teachers play an important role in facilitating the ethical and moral development of students through daily interactions and learning activities at school. The results of this research can be a basis or consideration for developing educational policies that focus more on the role of teachers in shaping the character and morals of students in the school environment. This implication includes efforts to increase the role and support of teachers in integrating ethical and moral values ​​in the curriculum and daily activities at school. Keywords: Teacher's Role; Ethical Values; Moral